La obra exapropiada. Derrida y las artes visuales - Galard, Jean (Escritura e Imagen, 2006)
The artworks, especially those included among the so called “visual arts”, they are seen nowadays surmised as a large quantity of appropriational effects. The political institutions, the museums, as well as the “specialists” –the art historian or the museum’s curator- put in action these effects through their own actions and competences. All of that, not just speaking about the gesture of the signature or the politics of the name regarding the author, or also about this hermeneutic operation that means the proper sense, and the ownership of the meaning exposed in the artwork. To this question, the mind of Jacques Derrida thinks of an inapropriable instance in the artwork, a kind of invisibility operating in the visual arts that makes nevertheless possible all these effects of appropriation. To this complex movement of misappropriation implicit in the sign that appropriates the artwork, or about the artwork, Jacques Derrida gives the name of expropriation. The artwork is always expropriated artwork.